Analisis Risiko Keterlambatan Proyek Menggunakan Metode House of Risk - Soetjipto, Jojok Widodo; Qudsy, Naahila Hunafaa; Arifin, Syamsul (Journal of Applied Civil Engineering and Infrastructure Technology, 2021)
In the implementation of project development, problems often occur which cause the project to get obstacles, causing delays in project completion time and failure to achieve the project goals. Therefore, it is necessary to research risk analysis and effectively mitigate it to reduce the negative impact of delays. Currently, many studies analyze the risk of delays but are limited to risk assessment based on probability and impact, and mitigation is only carried out on the causal variables without paying attention to the agent of the delay. While in this study using the House of Risk (HOR) method which consists of 2 stages. The first stage (HOR-1) is to determine the main factors causing delays and the second stage (HOR-2) is to mitigate risk effectively to properly resolve the delay problem based on the delay agent. The results of the delay risk analysis using HOR obtained 6 delay events caused by 7 dominant agents/causes of delay based on the Pareto diagram. Recommendations for handling project delays that are effective can be carried out through 4 main mitigation efforts so that the impact of delays can be prevented or reduced.